Some results on the qualitative theory of semiflows - Preda, Ciprian; Preda, Petre (Bulletin of the Belgian Mathematical Society, Simon Stevin, 2011)
We point out some results on the qualitative theory of three-parameter semiflows by analyzing the stability of the associated linear skew-product semiflow. Extensions of the well-known theorems due to Datko, Pazy, Rolewicz are obtained. 2000 Mathematics Subject Classification : 34D05,47D06, 93D20. Key words and phrases: (nonlinear) semiflows, evolution families, uniformexponential stability, Datko theorem.